The bioenergetic “CK Clamp” technique detects substrate-specific changes in mitochondrial respiration and membrane potential during early VML injury pathology - McFaline-Figueroa, Jennifer; Hunda, Edward T.; Heo, Junwon; Winders, Elizabeth A.; Greising, Sarah M.; Call, Jarrod A. (Frontiers in Physiology, 2023)
Volumetric muscle loss (VML) injuries are characterized by non-recoverable loss of tissue resulting in contractile and metabolic dysfunction. The characterization of metabolic dysfunction in volumetric muscle loss-injured muscle has been interpreted from permeabilized myofiber respiration experiments involving saturating ADP levels and non-physiologic ATP:ADP concentration ratios. The extent to which this testing condition obscures the analysis of mitochondrial (dys) function after volumetric muscle loss injury is unclear. An alternative approach is described that leverages the enzymatic reaction of creatine kinase and phosphocreatine to assess mitochondrial respiration and membrane potential at clamped physiologic ATP:ADP ratios, “CK Clamp.” The objective of this study was to validate the CK Clamp in volumetric muscle loss-injured muscle and to detect differences that may exist between volumetric muscle loss-injured and uninjured muscles at 1, 3, 5, 7, 10, and 14 days post-injury. Volumetric muscle loss-injured muscle maintains bioenergetic features of the CK Clamp approach, i.e., mitochondrial respiration rate (JO2) titters down and mitochondrial membrane potential is more polarized with increasing ATP:ADP ratios. Pyruvate/malate/succinate-supported JO2 was significantly less in volumetric muscle loss-injured muscle at all timepoints compared to uninjured controls (−26% to −84%, p < 0.001) and electron conductance was less at day 1 (−60%), 5 (−52%), 7 (−35%), 10 (−59%), and 14 (−41%) (p < 0.001). Palmitoyl-carnitine/malate-supported JO2 and electron conductance were less affected following volumetric muscle loss injury. volumetric muscle loss-injury also corresponded with a more polarized mitochondrial membrane potential across the clamped ATP:ADP ratios at day 1 and 10 (pyruvate and palmitoyl-carnitine, respectively) (+5%, p < 0.001). This study supports previous characterizations of metabolic dysfunction and validates the CK Clamp as a tool to investigate bioenergetics in traumatically-injured muscle.